US-Elastography With Different Techniques for Thyroid Nodule Characterization: Systematic Review and Meta-analysis - Cantisani, Vito; De Silvestri, Annalisa; Scotti, Valeria; Fresilli, Daniele; Tarsitano, Maria Grazia; Polti, Giorgia; Guiban, Olga; Polito, Eleonora; Pacini, Patrizia; Durante, Cosimo; Grani, Giorgio; Isidori, Andrea M.; et al. (Frontiers in Oncology, 2022)
Background Thyroid nodules are frequent in adult population and thyroid cancer incidence has increased dramatically over the past three decades. The aim of this systematic review and meta-analysis was to evaluate the US-Elastosonography (USE) diagnostic performance in assessing the thyroid nodules malignancy risk. Methods PubMed and Embase databases were searched from January 2011 to July 2021. We extracted data from selected studies and calculated the overall diagnostic accuracy of qualitative USE, semi-quantitative USE and quantitative USE. Summary receiver operating characteristic (ROC) curve was elaborated to show the results. All statistical tests were performed using Metadisc and Medcal software package. Results Finally 72 studies with 13,505 patients and 14,015 thyroid nodules (33% malignant) undergoing elastography were included. The pooled sensitivity, specificity and AUC were 84%, 81%, and 0.89 respectively for qualitative USE; 83%, 80%, and 0.93 for semi-quantitative USE and 78%, 81% and 0.87, for quantitative USE. The qualitative and semiquantitative USE present very similar diagnostic accuracy values and both better than the quantitative USE. Conclusions USE is a useful imaging tool for thyroid nodule characterization. In accordance with recent guidelines and meta-analyses, the USE could be used daily in thyroid nodule malignancy risk stratification. Systematic Review Registration PROSPERO: CRD42021279257.